SOFT SKILLS ABILITY OF EDUCATED YOUTH OF THE FACULTY OF ECONOMICS AND BUSINESS, UNIVERSITAS BRAWIJAYA ACADEMIC YEAR 2016 - Ade Ayu Laraswati (Jurnal Ilmiah Mahasiswa FEB, 2019)
This research aims to capture the soft skills ability of educated young generation of the Faculty ofEconomics and Business Universitas Brawijaya academic year 2016 by using seven indicators variablesnamely communication skills, critical thinking and problem-solving skills, teamwork, lifetime learning, andinformation management skills, entrepreneurship, ethics, morals, and professionalism, and leadership. Thesubjects of the research were students of the Faculty of Economics and Business Universitas Brawijayaacademic year 2016 who are taking minor thesis course. The questionnaire used as the research instrument.Using the purposive sampling method, this research focused on 290 respondents. The research data wereanalyzed using quantitative descriptive analysis with a percentage. In conclusion, the student’s soft skillsability of the Faculty of Economics and Business Universitas Brawijaya academic year 2016 are includedin the moderate category. Keywords: soft skills, student, educated youth